Senegal : School Autonomy and Accountability - World Bank (Washington, DC, 2014)
Senegal has accelerated the decentralization of education since 1996. Budgetary autonomy is latent. Autonomy over the management of operational budgets has been delegated to the communes, but salaries for teachers are managed at the central level. Autonomy in personnel management is latent. Both school directors and teachers are appointed at the central level. The role of the school councils in school governance is latent. There are two types of standardized student assessments, one at the national and one at the departmental level. The government spent 6 percent of Gross Domestic Product (GDP) in 2009 and 19 percent of its overall budget on education in 2008. School autonomy and accountability are key components of an education system that ensure educational quality. The transfer of core managerial responsibilities to schools promotes local accountability; helps reflect local priorities, values, and needs; and gives teachers the opportunity to establish a personal commitment to students and their parents. There are five policy goals for school autonomy and accountability. Below are the main indicators that can help benchmarking an education system's policies that enable school autonomy and accountability: school autonomy in the planning and management of the school budget; school autonomy in personnel management; role of the school council in school governance; school and student assessments; and accountability. This report focuses specifically on policies in the area of school autonomy and accountability.